Near-Infrared Fluorescent Agent for In Vitro Screening of Endometrial Cancer and Precancerous Lesions - Liang, Dongxin; Tuo, Xiaoqian; Wang, Qing; Zhao, Lanbo; Zhang, Kailu; Wang, Yiran; Feng, Xue; Yin, Panyue; Guo, Lin; Liu, Yu; Wang, Lei; Han, Lu; et al. (Frontiers in Oncology, 2021)
The lack of cytopathologists delays the advancement of screening for endometrial cancer. It was urgent to develop a new dye for rapid diagnosis. Our study aimed to synthesize a targeted folate receptor-α near-infrared (NIR) fluorescent agent, folic acid-zwitterionic NIR fluorophore (ZW-FA), and explore the feasibility for screening of endometrial cancer and precancerous change. Folic acid was conjugated with zwitterionic NIR fluorophore. The preparation of ZW-FA was validated by 1H NMR, mass spectrometric, ultraviolet spectra and fluorescence spectra. ZW-FA was incubated with endometrial cytology samples obtained from patients who underwent dilation and curettage or total hysterectomy. Diagnostic utility was calculated by applying laser confocal microscope, Image-J and statistical models, such as enumeration, receiver operating characteristic curve, logistic regression, support vector machine and decision tree were used. The purity of ZW-FA was > 95% determined by 1H NMR. ZW-FA had the strongest absorption peak at 633 nm in ultraviolet spectra. Photostability of ZW-FA was over 8 hours. In clinical validation, a total of 92 patients were enrolled. The cut-off value of ZW-FA was 49 in enumeration, which was used to distinguish the type of samples. Indicators about diagnostic utility are as follows: sensitivity 90.77%, specificity 62.96%, false-positive rate 37.04%, false-negative rate 9.23%, positive predictive value 85.51% and negative predictive value 73.91%. The samples processed by ZW-FA did not affect further Hematoxylin-Eosin staining and pathological diagnosis. It was an effective cytologic strategy for in vitro diagnosis of endometrial cancer and precancerous change by using ZW-FA.